Response of spleen lymphocytes shortly after thymectomy in adult mouse (Revista Española de Fisiología, 1977)
The blastogenesis response to the phytomitogens, PHA-P, Con A and PWM was used to assess the effect of adult thymectomy on the spleen lymphocytes of C57B1 mice. The mitogenic response to the phytomitogens was determined by 3H-thymidine uptake. The changes produced in theta-antigen bearing spleen lymphocytes were also evaluated making use of theta antibodies from AKR/S mice previously injected with splenic and thymic lymphocytes from CBA/J mice. The present results show that the response to mitogens PHA-P and Con A is reduced early after thymectomy while the response to PWM was only slightly reduced. There was not any correlation between the disminished response to mitogens and the changes observed in theta bearing spleen lymphocytes.